Kinetics and mechanism of photocatalytic degradation of rhodamine B on nanorod bismuth ferrite perovskite prepared by hydrothermal method - Kien Trung Chi,Thi Ha Nguyen; Chuc Ngoc Pham; Lim Thi Duong; Bac Quang Nguyen; Hung Bao Le; Mai Vu Ngoc Nguyen; Nhiem Ngoc Dao (My University, 2022)
Kinetics and mechanism of photocatalytic degradation of rhodamine B on nanorod bismuth ferrite perovskite prepared by hydrothermal method
Keywords: Bismuth ferrite